2013
DOI: 10.1111/jssr.12022
|View full text |Cite
|
Sign up to set email alerts
|

The Growing Social and Moral Conflict Between Conservative Protestantism and Science

Abstract: Abstract:Due to conservative Protestant elites challenging scientists in the public sphere, and prominent scientists attacking religion, scholars have claimed that there is an increasing conflict between conservative Protestants and science. However, these claims have never been empirically investigated and these general claims do not specify what conflict is actually about. In this paper

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
121
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(122 citation statements)
references
References 23 publications
(26 reference statements)
1
121
0
Order By: Relevance
“…First, some researchers suggest that there is a conflict between what is taught in colleges and universities and the content of certain religious beliefs (e.g., Beckwith 1985;Johnson 1997;Stark 1963). This "conflicting worldviews" argument emphasizes that higher education focuses on knowledge, learning, and science, while religion focuses on mystery and revelation (Miller 1967), and these are seen as incompatible approaches to the world (Halman and Draulans 2006), particularly in the conservative Protestant community (Evans 2013). Second, since social networks provide much of the impetus for religious practice and affilia tion (Cheadle and Schwadel 2012;Cornwall 1989;Iannaccone 1994), changes in social networks associated with higher education can lead to religious disaffiliation (Baker and Smith 2009;Maryl and Uecker 2011;Smith and Snell 2009).…”
Section: Changes In the College-educated Populationmentioning
confidence: 99%
“…First, some researchers suggest that there is a conflict between what is taught in colleges and universities and the content of certain religious beliefs (e.g., Beckwith 1985;Johnson 1997;Stark 1963). This "conflicting worldviews" argument emphasizes that higher education focuses on knowledge, learning, and science, while religion focuses on mystery and revelation (Miller 1967), and these are seen as incompatible approaches to the world (Halman and Draulans 2006), particularly in the conservative Protestant community (Evans 2013). Second, since social networks provide much of the impetus for religious practice and affilia tion (Cheadle and Schwadel 2012;Cornwall 1989;Iannaccone 1994), changes in social networks associated with higher education can lead to religious disaffiliation (Baker and Smith 2009;Maryl and Uecker 2011;Smith and Snell 2009).…”
Section: Changes In the College-educated Populationmentioning
confidence: 99%
“…They dissent on only a few scientific knowledge claims, like the origins of the earth and humans. Fundamentalists are, however, opposed to the social and moral influence of scientists (Evans, 2011;Evans, 2013). In general, religious Americans support science, but a science dedicated to solving concrete problems, not determining moral values or determining the purpose of humanity.…”
Section: The Religiousmentioning
confidence: 99%
“…Such information would be helpful in understanding whether the effects of fundamentalist religion represent a specific religiously based rejection of evolution or a more general anti-science world view (Gauchat 2008). Indeed, previous studies have indicated that religious rejection of evolution and distrust of the scientific community are linked to one another (Evans 2011(Evans , 2013, particularly as a result of the perceived moral and social implications of Darwinian evolution.…”
Section: Study Limitationsmentioning
confidence: 99%